Rancang Bangun Prototipe Mesin Cuci Mobil Otomatis Berbasis Arduino - Fadillah, Rizqi; ARIS BUDIMAN,, ST,MT (2017)
Abstract In this research, author design a prototype of Arduino based automatic car washer. Car is one of transportation is very important thing for the car, such as car washing. By car washing, paint and the body will always be in good condition, and the corrossion can be prevented. Today, many people don't have enough time to do that by themselves, so they will pay another people to do feel their nedd. Beside that about car wash need fast, efficient, and good quality service, but affordable price. The objective of this reserch is to design an automatic car wash prototype to faster the process but still in good quality wash. The design use conveyor that equipped by several infrared sensors and barrier to detect object. The mschine is controlled by Arduino and power by 12 Volt DC source.The first experiments with the data PWM 80 conveyor moves very slowly and slip on the wheels connected to the motor, to experiment with the data PWM 2 180, koveyor began to stabilize and does not slip as in the first experiment. Experiment to 5 with PWM data is 240, the conveyor moves faster than the first trial until the fifth trial. Last experiment with maximum PWM data is 255, the fastest conveyor speeds of various experiments conducted, thus making the car washing process into short. Keywords: Arduino, Infrared Sensors, Conveyor